Analytical study of the implications of the adoption of IFRS 9 on the credit and financing policies of Arab banks - Mohammed, Salah Ali Ahmed; Hamed, Mahjoub Abdullah (Journal of Economic, Administrative and Legal Sciences, 2017)
The objective of this study was to analyze the anticipated effects of the application of the International Financial Reporting Standard (IFRS9), which replaced the International Standard ( IAS 39), on the Arab banks. The obligatory application of the new standard will take place on the beginning of 2018. The application requirements of this standard constitute a great challenge to the Arab banks, in the fields of credits, finance and the banking and accounting systems. The study represented the International Financial Reporting Standard (IFRS 9) and the requirements of classification and measurement of the obligations, with special focus on the differences between the two standards. The study as well, focused on the challenges which face the standard application and the effect of this application on the banking system, with special focus on the expected credits loss (ECL). The study represented examples of some Arab banks experiences and evaluated these experiences. The study has come out with some results, including that the change of the (ECL) model will create some impediments on the credit and finance policies of the Arab banks, whereas the standard (IFRS9) will strengthen the shareholders and depositors trust, because it adopts a perceptional policy which avoids the expected loss which, in turn, reduces the liquidity risk and the failure of the obligations payment. The study also proposed some recommendations.
Keywords: IAS39; policies; credit; financing; Arab banks